2020
DOI: 10.1002/jbmr.4092
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of BMP Signaling Prevents Hyperthyroidism-Induced Bone Loss in Male Mice

Abstract: Thyroid hormones (TH) are key regulators of bone health, and TH excess in mice causes high bone turnover-mediated bone loss. However, the underlying molecular mechanisms of TH actions on bone remain poorly defined. Here, we tested the hypothesis whether TH mediate their effects via the pro-osteogenic bone morphogenetic protein (BMP) signaling pathway in vitro and in vivo. Primary murine osteoblasts treated with 3,3 0 ,5-triiodo-L-thyronine (T 3) showed an enhanced differentiation potential, which was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 69 publications
1
21
1
2
Order By: Relevance
“…This finding indicated that bone resorption in the mice with thyrotoxicosis increased significantly, and supplementation with vitamin D reduced the number of osteoclasts in these mice. In addition, the micro-CT results showed that the BMD of the lumbar vertebrae and femur in the mice with thyrotoxicosis decreased and the bone architecture was destroyed, which was similar to the findings of most studies ( 18 , 19 ). Treatment with vitamin D significantly improved the BMD and trabecular bone architecture of the lumbar vertebrae and femur in the mice with low LT4-induced thyrotoxicosis.…”
Section: Discussionsupporting
confidence: 87%
“…This finding indicated that bone resorption in the mice with thyrotoxicosis increased significantly, and supplementation with vitamin D reduced the number of osteoclasts in these mice. In addition, the micro-CT results showed that the BMD of the lumbar vertebrae and femur in the mice with thyrotoxicosis decreased and the bone architecture was destroyed, which was similar to the findings of most studies ( 18 , 19 ). Treatment with vitamin D significantly improved the BMD and trabecular bone architecture of the lumbar vertebrae and femur in the mice with low LT4-induced thyrotoxicosis.…”
Section: Discussionsupporting
confidence: 87%
“…According to this, the BMP antagonist noggin ameliorated osteoclast formation through its effects on stromal cell/osteoblast differentiation (Abe et al, 2010). Recently, we demonstrated reduced osteoclast numbers in mice treated over 4 weeks with ALK3-Fc, a recombinant fusion protein that specifically scavenges BMPR1A/ALK3-activating BMP ligands (Lademann et al, 2020). However, due to systemic drug application it is unclear whether osteoclasts are affected in a direct or indirect manner as ALK3-Fc is reported to enhance OPG and reduce RANKL levels in serum of treated mice as well as in SaOS2 cells (Baud'huin et al, 2012).…”
Section: Bmps As Mediators Between Bone Resorption and Bone Formationmentioning
confidence: 97%
“…The expression of differentiation markers was increased, and Smad1/5/8 phosphorylation was mediated by BMP signaling when osteoblasts were treated with T3. This finding suggested that THs could promote osteoblast differentiation via the BMP/Smad signaling pathway ( 44 ). C2C12 myoblasts were transfected with a BMP/Smad-specific reporter construct and treated with Bmp2 or Wnt3a ligands, and the results showed that not only Bmp2 but also Wnt3a enhanced BMP/Smad activity.…”
Section: Effects Of Ths On Bonementioning
confidence: 99%
“…Therefore, sclerostin may be a potential therapeutic target in hyperthyroidism related osteoporosis ( 68 ). On the other hand, excessive activation of BMP and Wnt pathway were observed in hyperthyroidism, indicating that BMP or Wnt pathway may be other therapeutic targets for hyperthyroidism-induced bone loss ( 44 , 69 ).…”
Section: Thyroid Dysfunction (Hyperthyroidism and Hypothyroidism) Act...mentioning
confidence: 99%